"It's all about acceptance": A qualitative study exploring a model of positive body image for people with spinal cord injury. (September 2015) - Bailey, K. Alysse; Gammage, Kimberley L.; van Ingen, Cathy; Ditor, David S.
Highlights: Positive body image experiences were explored in people with spinal cord injury. The core categories found were body acceptance, appreciation, and gratitude. Positive body image characteristics consistent with previous research were noted. Distinct positive body image characteristics specific to spinal cord injury emerged. Findings suggest universal experiences underlying positive body image. Abstract: Using modified constructivist grounded theory, the purpose of the present study was to explore positive body image experiences in people with spinal cord injury. Nine participants (five women, four men) varying in age (21–63 years), type of injury (C3-T7; complete and incomplete), and years post-injury (4–36 years) were recruited. The following main categories were found: body acceptance, body appreciation and gratitude, social support, functional gains, independence, media literacy, broadly conceptualizing beauty, inner positivity influencing outer demeanour, finding others who have a positive body image, unconditional acceptance from others, religion/spirituality, listening to and taking care of the body, managing secondary complications, minimizing pain, and respect. Interestingly, there was consistency in positive body image characteristics reported in this study with those found in previous research, demonstrating universality of positive body image. However, unique characteristics (e.g., resilience, functional gains, independence) were also reported demonstrating the importance of exploring positive body image in diverse groups.